2006
DOI: 10.1161/01.atv.0000237629.29842.4c
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage ABCG1 Deletion Disrupts Lipid Homeostasis in Alveolar Macrophages and Moderately Influences Atherosclerotic Lesion Development in LDL Receptor-Deficient Mice

Abstract: Objective-ABCG1 has recently been identified as a facilitator of cellular cholesterol and phospholipid efflux to high-density lipoprotein (HDL). Its expression in macrophages is induced during cholesterol uptake in macrophages and by liver X receptor (LXR). The role of macrophage ABCG1 in atherosclerotic lesion development is, however, still unknown. Methods and Results-To assess the role of macrophage ABCG1 in atherosclerosis, we generated low-density lipoprotein (LDL) receptor knockout (LDLr Ϫ/Ϫ ) mice that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
139
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 185 publications
(148 citation statements)
references
References 29 publications
4
139
2
3
Order By: Relevance
“…11 Recently, 3 groups reported transplantation studies of ABCG1-deficient (ABCG1 Ϫ/Ϫ ) bone marrow into LDL receptor-deficient mice with apparently contrasting effects on atherosclerotic lesion formation. [12][13][14] In agreement, both Out et al 12 and Baldán et al 13 observed severe lipid deposition in the macrophages of the lungs of LDL receptor-deficient mice receiving ABCG1 Ϫ/Ϫ bone marrow. Out et al showed in LDL receptor-deficient mice a moderate protection of macrophage ABCG1 on atherosclerotic lesion formation (33% to 36%) both at 6 and 12 weeks on a Western-type diet containing 15% fat and 0.25% cholesterol.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…11 Recently, 3 groups reported transplantation studies of ABCG1-deficient (ABCG1 Ϫ/Ϫ ) bone marrow into LDL receptor-deficient mice with apparently contrasting effects on atherosclerotic lesion formation. [12][13][14] In agreement, both Out et al 12 and Baldán et al 13 observed severe lipid deposition in the macrophages of the lungs of LDL receptor-deficient mice receiving ABCG1 Ϫ/Ϫ bone marrow. Out et al showed in LDL receptor-deficient mice a moderate protection of macrophage ABCG1 on atherosclerotic lesion formation (33% to 36%) both at 6 and 12 weeks on a Western-type diet containing 15% fat and 0.25% cholesterol.…”
supporting
confidence: 59%
“…Out et al showed in LDL receptor-deficient mice a moderate protection of macrophage ABCG1 on atherosclerotic lesion formation (33% to 36%) both at 6 and 12 weeks on a Western-type diet containing 15% fat and 0.25% cholesterol. 12 In contrast, Baldán et al observed an increase in lesion formation of 35% to 40% with mice fed a diet with 21% fat and 1.25% cholesterol for 12 weeks, 14 whereas Ranalletta et al found in mice on a 42% fat diet at 7 weeks no effect on lesion formation and at 11 weeks a 32% increase in lesion area in the presence of macrophage ABCG1. 14 These different results are discussed in an editorial by Curtiss.…”
mentioning
confidence: 95%
“…Foam cell formation occurs mainly as a result of an imbalance between lipid binding/uptake and efflux in macrophages, which results in excessive lipoprotein‐derived cholesterol accumulation inside macrophages. It is well‐known that lipid binding/uptake is mediated by various receptors including SR‐A and CD36,50, 51 while the efflux of accumulated cholesterol in macrophages is mainly controlled by reverse cholesterol transporters including SR‐BI,52 ABCA153 and ABCG1 54. Our data show that the ABCA1 protein, but not the SR‐BI and ABCG1 proteins, is altered in NE‐deficient macrophages or affected by addition of exogenous HNE, indicating that ABCA1 is selectively responsible for NE‐promoting foam cell formation.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of free cholesterol and cholesteryl esters was determined by the use of enzymatic colorimetric assays as described by Out et al . (2006). The concentration of TGs, free cholesterol and cholesteryl esters was corrected for the total protein concentration, determined using a Pierce™ BCA Protein Assay Kit (ThermoFisher Diagnostics, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%